2017
DOI: 10.1007/s40429-017-0144-0
|View full text |Cite
|
Sign up to set email alerts
|

Four Mechanistic Models of Peer Influence on Adolescent Cannabis Use

Abstract: Purpose of review Most adolescents begin exploring cannabis in peer contexts, but the neural mechanisms that underlie peer influence on adolescent cannabis use are still unknown. This theoretical overview elucidates the intersecting roles of neural function and peer factors in cannabis use in adolescents. Recent findings Novel paradigms using functional magnetic resonance imaging (fMRI) in adolescents have identified distinct neural mechanisms of risk decision-making and incentive processing in peer contexts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 105 publications
0
17
0
1
Order By: Relevance
“…Previous studies investigating social influence in young people have often focused on negative outcomes, such as dangerous risktaking or antisocial behaviour. For example, studies have examined the effect of social influence on adolescents' driving risks (Chein et al, 2011;Gardner & Steinberg, 2005), substance use (Caouette & Ewing, 2017;Lundborg, 2006) and risk perception (Knoll et al, 2015). Studies that have compared age groups have found that susceptibility to these types of social influence is high in childhood and/or adolescence and then decreases with age (Chein et al, 2011;Gardner & Steinberg, 2005;Knoll et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies investigating social influence in young people have often focused on negative outcomes, such as dangerous risktaking or antisocial behaviour. For example, studies have examined the effect of social influence on adolescents' driving risks (Chein et al, 2011;Gardner & Steinberg, 2005), substance use (Caouette & Ewing, 2017;Lundborg, 2006) and risk perception (Knoll et al, 2015). Studies that have compared age groups have found that susceptibility to these types of social influence is high in childhood and/or adolescence and then decreases with age (Chein et al, 2011;Gardner & Steinberg, 2005;Knoll et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Greater self‐focus also has a darker side. It can lead to rumination, negative affect, and depression (Moberly and Watkins, ; Nolen‐Hoeksema, ), and can contribute to adolescents’ sense that they need to engage in otherwise risky behaviors to improve their social standing and affect, including through the use of substances (Caouette and Feldstein Ewing, ; Cousijn et al., ).…”
Section: The Nature Of the Adolescent Brain: Characteristic Features mentioning
confidence: 99%
“…Given that peer substance use is one of the major determinants of escalation of use and subsequent transition to long-term substance use disorders, 14,15 increased social neural attunement to peers during adolescence is highly likely to be a primary risk candidate. 35,5254 A behavioural study 55 in this domain suggests a social contagiousness around substance use, whereby peer-to-peer use is transmitted through shared social norms (eg, “My friends are all using, so why shouldn’t I?”) and prototypes (eg, heavy drinkers being perceived as cool). This social contagiousness is further reflected by studies showing peer-to-peer imitation of drinking behaviour in semi-naturalistic bar laboratory settings 56,57 and on social media, in which celebration of pro-drinking behaviours by peers has been connected to shifts in young people’s own perceptions of the risks or benefits of substance use.…”
Section: Implications Of Adolescent Brain Development In the Context mentioning
confidence: 99%
“…58 Importantly, the social nature of adolescent substance use is highly multidimensional. 52 For some adolescents, social appraisal of substance use contributes to the development of new relationships and social status, reinforcing the value of substance use as positive and the rewarding aspects of use as social in nature. Some adolescents might use substances in peer settings to prevent negative peer feedback, anticipated peer rejection, or social anxiety, rendering a negative social reinforcement of substance use.…”
Section: Implications Of Adolescent Brain Development In the Context mentioning
confidence: 99%